PERAN MASYARAKAT DALAM PENYELENGGARAAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Siti Asha Chairani; Julia Yana; Nur Ilham; Opi Andriani (JOURNAL SAINS STUDENT RESEARCH, 2024)
Existing inclusive education has not been implemented optimally. People do not understand the inclusive education model so they have not been able to participate in it. Community participation is an important component of the success of inclusive education. Because inclusive schools require collaboration between the community and classroom teachers to create and sustain a warm classroom community, embrace diversity, and respect differences. The purpose of this study was to determine the role of the community in the implementation of inclusive education in elementary schools. This research uses a qualitative approach through data collection through observation and interview. The results of this study show that various problems encountered in the role of the community in providing inclusive education in elementary schools are problems related to the lack of community understanding about inclusive education